Basic Students Learning Motivation Strategies in The Covid-19 Pandemic Time Through Study Groups - Lailasari, Ita (Devotion : Journal of Research and Community Service, 2020)
This study aims to determine strategies in increasing student learning motivation to maintain the continuity of the educational process in the Study From Home (SFH) policy during the COVID-19 pandemic. The method used in this research is qualitative with the research subject, namely students in the study group in Jungjang village. Data collection techniques used were interviews and documentation. The results showed that the form of the learning group teacher strategy to increase student learning motivation in the SFH policy in the midst of the COVID-19 outbreak was with student work study groups which were proven to increase student learning motivation. The obstacles encountered by the learning group teacher were related to the aspects of the students' parents, learning facilities, and the creativity of the learning group teachers. The benefits of this research are the growth of student learning motivation, train student discipline, and help improve the closeness between parents and children.